Global Value Chains Research in Development and Business Economics: A Bibliometric Study of Trends and Themes - Loso Judijanto; Noor Aziz; Titis Nistia Sari; Rusli Hereng; Fida Arumingtyas (Eastasouth Institute, 2026)
This study aims to analyze the development of global value chains (GVC) research within the fields of development and business economics using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to identify publication trends, influential articles, collaboration networks, and thematic structures. The results show a consistent increase in the number of publications, indicating growing academic interest in GVC. Citation analysis reveals that highly influential studies are dominated by themes related to digital transformation, sustainability, and global economic systems. Co-authorship analysis highlights the presence of key scholars who act as central connectors within research networks, although collaboration remains partially fragmented. Meanwhile, co-occurrence analysis demonstrates that recent research increasingly integrates topics such as sustainable development, circular economy, and innovation. Overall, the findings suggest that GVC research has evolved into a multidisciplinary field that combines economic, environmental, and technological perspectives. This study contributes to the literature by providing a comprehensive mapping of research trends and identifying future directions for GVC studies.